Developing and Testing a Middle-Range Theory of the Well-Being Supportive Physical Environment of Home-Dwelling Elderly. (15th May 2013) - Elo, Satu; Kääriäinen, Maria; Isola, Arja; Kyngäs, Helvi
Abstract : The aim is to describe the development of a middle-range theory by using an inductive-deductive approach. A theory of well-being supporting physical environment of home-dwelling elderly is used as an example. The inductive-deductive theory development process is described through four different phases: (1) the creations of concepts were described inductively through concept synthesis, (2) relationships between the concepts were examined to set up a hypothetical model, (3) hypotheses were set up to verify the concepts and to test hypothetical models, and (4) the verification and presentation of the theory.